The Use of Patient-Reported Outcomes in Clinical Practice: A National Survey of Hand Surgeons - Stephanie Choo, MD; Rown Parola, MD; Benjamin Kirby, MD; Daniel A. London, MD (Journal of Hand Surgery Global Online)
Purpose: Patient-reported outcome measures (PROMs) use in practice could be limited secondary to logistical constraints and lack of consensus regarding PROMs’ clinical value. Therefore, the goals of this study are to determine (1) the use of PROMs by practicing hand surgeons, (2) which questionnaires are most used and the purpose for collection, and (3) the barriers to use. Methods: A survey of American Society for Surgeons of the Hand members was conducted in May 2023. Demographic data of respondents, PROMs collected, and implementation and barriers to use were assessed. Associations between variables were determined by Fischer exact tests and logistic regression. Results: A total of 419 surveys were completed from the 4,523 individuals contacted, representing a 9.3% response rate. Eighty-one percent (81%) were US/Canadian respondents, and 19% reported as other nationalities, with other nationalities reporting use of PROMs at a higher rate than US/Canadian respondents. Odds of PROM use were higher for academic, hybrid, and hospital employed respondents relative to those in private practice settings. The 247 (58%) respondents who did not use PROMs cited barriers including logistic or administrative concerns, uncertainty on application in practice, having no interest, and cost concerns. The most frequently used upper-extremity questionnaire among the 172 (42%) respondents using PROMs was the QuickDASH (Disabilities of the Arm, Shoulder, and Hand), which was used by 112 respondents (65.1%). Patient-reported outcome measures were collected for research/database purposes by 130 (76%) and monitoring routine clinical care by 103 (60%). Among those using PROMs for clinical care, 79 (77%) of respondents use PROMs for postoperative recovery monitoring and 52 (55%) for counseling regarding surgical expectations. Conclusions: Patient-reported outcome measure use varies by practice setting, with most respondents not collecting PROMs. There remains large variability in the application of PROMs, and further research is needed to determine and demonstrate the value of PROMs in hand surgery for routine clinical care. Type of study/level of evidence: Prognostic IIc.